Passiflora bernaccii (Passifloraceae s.s.), a new species from Acre, Brazil - Mezzonato-Pires, Ana Carolina (Phytotaxa, 2018)
Passiflora bernaccii is described and illustrated here as a new species belonging to P. subgenus Astrophea section Pseudoastrophea from the Brazilian Amazon Rainforest. The new species has similarities with P. hexagonocarpa, P. rhamnifolia and P. tessmannii, but differs mainly by the shape of the outer filaments of the corona, shape of the operculum and presence of trochlea. Palynological support for the classification is also discussed.